Electronic Information Sharing Between Nursing and Adult Social Care Practitioners in Separate Locations: A Mixed-Methods Case Study. (2021) - Chester, Helen; Hughes, Jane; , Ian Bowns; Abendstern, Michele; Davies, Sue; Challis, David
No abstract available